Experimental Validation Of A Dual Loop Control Of Two Phases Interleaved Boost Converter For Fuel Cell Applications - Kraa, O.; Ghodbane, H.; Saadi, R.; Ayad, M. y.; Becherif, M.; Bahri, M.; Aboubou, A. (University of Eloued جامعة الوادي, 2016)
In this paper, a modelling, an implementation and a control of a dc-dc converter structure called “two phases Interleaved Boost Converter (IBC)” will be presented. This topology is widely used in order to reduce the input current ripples and the size of passive component with high efficiency. The control of the IBC converter is designed by dual loop control that contains a voltage loop with a linear PI controller and a fast current loop with a non-linear sliding controller to ensure a good tracking in steady state and fast performance in transient state. The proposed control loop has been validated, first by the simulation results under Matlab-Simulink and after by the experimental results using a small-scale test bench with the dSPACE-1104 card.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 02
Keywords: Interleaved Boost Converter; fuel cell; PI; sliding mode control.